Credit Scoring System Using Machine Learning - Abhishek Kumar; Abhijeet Kumar; Aditya Kumar Singh; Ms. Nikita (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This research paper offers a comprehensive examination of credit scoring systems. We will explore the current methodologies employed, the challenges encountered, and potential avenues for improvement. Credit scoring plays a critical role in financial decision-making, impacting both individual access to credit and lender risk management strategies. The paper will analyze traditional credit scoring models alongside emerging trends designed to enhance the accuracy and fairness of credit assessments. Additionally, we will discuss the ethical considerations surrounding credit scoring and propose recommendations for future advancements.